Lamb the gospel according to Biff, Christ's childhood pal - Moore, Christopher, 1957- (New York : HarperAudio, 2002)
Adult/High School-An angel has resurrected Levi bar Alpheus, known as Biff, to tell this story of his life with Joshua, better known to the modern world as Jesus Christ. As youths, they travel to the East in search of the wise men who gave gifts to Joshua at his birth, because the young man has a problem: he knows he's the Messiah, but he doesn't know what to do about it. Along the way, he and Biff come in contact with the spirituality of the East, along with a smattering of martial arts, strange poisons, abominable snowmen, and more. The story concludes with their return to Israel and Biff's own explanation of the events that make up the traditional gospel narrative. Readers who might be offended by the author's casual treatment of Christian themes may also take umbrage at his treatment of Judaism, Buddhism, Taoism, Hinduism, and much else. However, the author manages to share a variety of the world's spiritual insights while creating interesting and vivid characters. The style is smooth, drawing readers into the story seamlessly except for the need to laugh out loud every page or two. The humor is good-natured, despite the fact that Biff claims to be the inventor of a practice known as "sarcasm." In an excellent afterword, the author explains the choices he made in writing the novel, which will fascinate would-be writers, as well as provide a rebuttal for the book's likely critics.-Paul Brink
Keywords: Jesus Christ -- Fiction; Jesus Christ -- Friends and associates -- Fiction; Bible -- History of Biblical events -- Fiction; Humorous fiction; Christian fiction